Use a transformation to solve the equation.



h + (–3) = –0.6

Question 3 options:

h = –2.4

h = 2.4

h = –3.6

h = 3.6

1 answer

To solve the equation h + (-3) = -0.6, we can use a transformation to isolate h.

Adding 3 to both sides of the equation will eliminate the -3 on the left side:
h + (-3) + 3 = -0.6 + 3
h = 2.4

Therefore, the solution to the equation is h = 2.4.
Similar Questions
  1. Use a transformation to solve the equation.z – (–0.3) = –2.4 Question 2 options: z = –2.7 z = 2.7 z = –2.1 z = 2.1
    1. answers icon 1 answer
  2. Use a transformation to solve the equation.n + 11.5 = –29 Question 5 options: n = –17.5 n = 40.5 n = 17.5 n = –40.5
    1. answers icon 1 answer
  3. Use a transformation to solve the equation.Mathml image Question 4 options: w = –32 w = –2 w = 2 w = 32
    1. answers icon 1 answer
  4. Use a transformation to solve the equation.Mathml image Question 4 options: w = –32 w = –2 w = 2 w = 32
    1. answers icon 1 answer
more similar questions